KESALAHAN PENGGUNAAN PREFIKS DI– PADA BERITA ONLINE JAWA POS TAHUN 2023 - Lisa Kusumawardani; Suhartono; Trinil Dwi Turistiani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
News manuscripts before being published go through an editing process. This is done to minimize word error and making it easier for readers to understand. This study aims to describe the misuse of the di- prefix in Jawa Pos online news. This study is classified as a qualitative research by analyzing obtained data. The research data is in the form of words that use prefixes in news articles published by Jawa Pos Digital. Articles published from 25 February to 19 April 2023 are used as data sources. Data analysis techniques in this study uses three stages, (1) data collection, (2) data analysis, and (3) conclusion. Results from this study showed nine misuses of the di- prefix in online news articles, three misuses of the di- prefix followed by a place word and six misuses of the di- prefix followed by a noun. These misuses are classified into (1) combining the di- prefix followed by a place word and (2) seperating the di- prefix followed by a verb.